Leaders Like Us: Supporting Inclusivity and Accessibility in Female Physical Activity Leadership (Baltic Journal of Sport and Health Sciences, 2026)
Background: The United Kingdom physical activity workforce remains predominantly White and male, contributing to lower participation rates among young females from underserved communities. Research highlights the significance of relatable role models in engaging inactive populations, particularly those sharing characteristics including gender, ethnicity, and socioeconomic status. However, evidence-based programmes explicitly designed to empower young females from underserved backgrounds in broader physical activity contexts beyond traditional sports remain scarce. This research, part of the Leaders Like Us project, aims to systematically map and critically analyse UK-based programmes to understand effective engagement, support, and development mechanisms for these young female leaders.Methods: This study employed a mixed-methods approach. Firstly, systematic mapping identified, categorised, and evaluated existing young physical activity leader programmes across the United Kingdom. This included assessing programme objectives, recruitment strategies, engagement mechanisms, and outcomes, with a critical focus on programme mechanisms for supporting underserved youth. Secondly, qualitative focus groups with stakeholders, sport development practitioners, with between 3 and 15 years of experience developing young people as physical activity leaders, explored effective strategies, challenges, and best practices in engaging underserved female groups.Results: Findings revealed few programmes specifically target underserved young females or extend beyond traditional sport settings. Programmes frequently lacked appropriate mechanisms to engage young people experiencing multiple intersecting markers of disadvantage. Effective engagement strategies included targeted outreach, culturally competent programme design, accessible locations, and peer-led mentorship. Key mechanisms for sustained participation involved building confidence, ensuring safe and inclusive environments, and aligning activities with participants’ lived experiences. Programmes articulating clear outcomes related to personal growth, leadership skills, and social impact demonstrated greater sustainability potential.Conclusion: This study advances understanding of inclusive leadership development in physical activity contexts. By highlighting successful recruitment strategies, engagement processes, and practitioner recommendations, the research provides actionable insights for practitioners and policymakers aiming to enhance inclusivity and sustainability in physical activity leadership, ultimately promoting sustained participation among underserved young females.